Mountains - Arnold, Quinn M. (Mankato, MN : Creative Education, 2016)
"A kindergarten-level introduction to mountains, covering their climate, plant and animal life, and such defining features as their rocky peaks"--
Hello, mountain! -- Tall rocks -- Big mountain animals -- Mountain base -- Mountain peak -- The tallest mountain -- Small mountain animals -- Goodbye, mountain! -- Picture a mountain.
Includes index.
Keywords: Mountains -- Juvenile literature; Mountain ecology -- Juvenile literature